1987
DOI: 10.1111/j.0954-6820.1987.tb10684.x
|View full text |Cite
|
Sign up to set email alerts
|

Treatment with One‐alpha‐hydroxycholecalciferol in Middle‐aged Men with Impaired Glucose Tolerance—A Prospective Randomized Double‐blind Study

Abstract: Experimental evidence suggests a specific role for the active metabolite of vitamin D (1,25(OH)2D3) in insulin secretion. In order to evaluate the possible clinical significance, 65 middle‐aged men with impaired glucose tolerance, and normal serum levels of vitamin D metabolites, were enrolled in a three‐month study where they were given either 0.75 μg alpha‐calcidol (1α(OH)D3) daily or placebo. Indices of glucose and lipid metabolism were evaluated before and after treatment. There were no significant changes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
53
0
5

Year Published

1995
1995
2016
2016

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 80 publications
(63 citation statements)
references
References 18 publications
3
53
0
5
Order By: Relevance
“…3). Vitamin D supplementation did not reduce HbA 1c compared with placebo in these studies (between-group difference 0.3 mmol ⁄ mol, 95% CI )2.0 to 2.5 (0.03%, 95% CI )0.18 to 0.23%); I 2 = 0%, 95% CI 0-0%); omission of one study using 1-alpha hydroxylated vitamin D derivatives [23] showed a similar effect [between-group difference 0.3 mmol ⁄ -mol, 95% CI )2.2 to 2.7 (0.03%, 95% CI )0.20 to 0.25%)].…”
Section: Fasting Glucosementioning
confidence: 83%
See 1 more Smart Citation
“…3). Vitamin D supplementation did not reduce HbA 1c compared with placebo in these studies (between-group difference 0.3 mmol ⁄ mol, 95% CI )2.0 to 2.5 (0.03%, 95% CI )0.18 to 0.23%); I 2 = 0%, 95% CI 0-0%); omission of one study using 1-alpha hydroxylated vitamin D derivatives [23] showed a similar effect [between-group difference 0.3 mmol ⁄ -mol, 95% CI )2.2 to 2.7 (0.03%, 95% CI )0.20 to 0.25%)].…”
Section: Fasting Glucosementioning
confidence: 83%
“…In those with abnormal glucose tolerance, there was a small but significant reduction in fasting glucose in the vitamin D group compared with placebo ()0.32 mmol ⁄ l, 95% CI )0.57 to )0.07, P = 0.01), with no significant heterogeneity (I 2 = 0%, 95% CI 0-67%). Omitting studies using 1-alpha hydroxylated vitamin D compounds [23,24] did not change these results (between-group difference 0.01 mmol ⁄ l, 95% CI )0.07 to 0.09 for the group with normal fasting glucose; )0.35 mmol ⁄ l, 95% CI )0.61 to )0.08 for the group with abnormal glucose tolerance); similarly, omitting the largest study [23] did not change the point estimate in the group with abnormal glucose tolerance ()0.30 mmol ⁄ l, 95% CI )0.90 to 0.30). Omitting studies where calcium was administered [25][26][27] similarly did not change the outcome in either the group with normal fasting glucose (difference = 0.01 mmol ⁄ l, 95% CI )0.21 to 0.23) or in the group with abnormal glucose tolerance ()0.30 mmol ⁄ l, 95% CI )0.90 to 0.30).…”
Section: Fasting Glucosementioning
confidence: 99%
“…Specifically, there have been a small number of human clinical studies in which an association between baseline vitamin D status and subsequent weight loss success was identified. For example, Ljunghall et al 89 reported, as a secondary finding in a study designed to investigate the effect of vitamin D supplementation on insulin secretion, that subjects who received low-dose vitamin D (cholecalciferol) supplementation showed a small but significant loss of body weight as compared with subjects receiving placebo. Ortega et al 90 observed in a hypo-caloric weight loss intervention study that baseline serum 25-hydroxyvitamin D was a strong predictor of weight loss.…”
Section: Methodsmentioning
confidence: 99%
“…Only two studies used a more sophisticated method for assessment (intravenous glucose tolerance test) (8,10). Regarding insulin sensitivity, a few studies have reported an improvement in insulin sensitivity (13,14), but several did not (8,12,(15)(16)(17)(18)(19).…”
Section: Serum 25-oh-vitamin D [25(oh)d]mentioning
confidence: 99%